The effects of perceived usefulness, perceived ease of use, and trust on online sales performance in the refrigeration product sector - Ha, Doan Thi Thu; Thinh, Mai Hoang; Long, Vu Le; Ha, Thai Van (Edelweiss Applied Science and Technology, 2026)
This study examines the effects of perceived usefulness (PU), perceived ease of use (PEOU), and trust (TRUST) on online sales performance (OSP) in the refrigeration product sector in Hanoi, Vietnam, within the context of digital transformation and e-commerce growth. Using primary data collected from 350 employees working in firms engaged in online sales, the study applies reliability analysis, exploratory factor analysis (EFA), and multiple regression using SPSS. The results indicate that all three factors have significant positive effects on OSP (p < 0.05), with perceived usefulness exerting the strongest influence (β = 0.353), followed by perceived ease of use (β = 0.224) and trust (β = 0.156). The model explains 37.4% of the variance in online sales performance (R² = 0.374). These findings highlight the importance of enhancing functional value, usability, and trust in digital platforms, particularly for high-value products such as refrigeration appliances. The study contributes to the literature by extending TAM and trust theory to a specific product category in an emerging market. Managerial implications suggest that firms should prioritize user-centered design, transparent service policies, and AI-enabled digital solutions to improve online sales performance. Future research should explore additional determinants and apply more advanced analytical approaches.